Good Grubbin': the development and evaluation of a nutrition-oriented cooking show on a college campus - Clifford, Dawn Elizabeth, author; Anderson, Jennifer, advisor; Auld, Garry, committee member; Harris, Mary, committee member; Miller, Jeffrey P., committee member; Champ, Joseph, committee member (Colorado State University. Libraries, 2006)
The college-aged population has unique barriers to adopting healthful eating habits and often lacks the knowledge, skills, and self-efficacy needed for basic meal planning. This is thought to contribute to students' diets which are inadequate in fruits and vegetables and high in dietary fat, cholesterol and sodium. Previous research supports that students prefer to obtain nutrition information through the mass media. The use of media channels on college campuses may be an un-tapped source for delivering health information to college students. The objective of this research was to determine an appropriate campus-specific mass media channel for delivering nutrition information and to develop and evaluate the impact of a televised cooking program on the diets of college students. A needs assessment survey was conducted with undergraduate students in a freshman-level core curriculum anthropology course to determine media channel preferences, and topic interests. While television was ranked as the most preferred media channel for obtaining nutrition information, the newspaper was the highest utilized campus-specific media channel. Students were more interested in reading articles on nutrition in the campus newspaper than using other proposed campus media sources. Of the 169 respondents, 87% reported interest in reading a weekly article about nutrition, exercise, and cooking techniques in the college newspaper. Students were most interested in gaining information from the media on meal planning, cooking, and shopping. Upon further exploration of developing a media-based nutrition intervention with the campus newspaper, campus media policies prevented the printing of a weekly newspaper column on nutrition. Based on students' interest in television as a medium for obtaining nutrition information, and the accessibility of the campus television station, this media channel was selected for a nutrition intervention. A pilot nutrition-oriented cooking program was developed in collaboration with the campus media station at Colorado State University. Students were recruited from a core curriculum health class to participate in four female and four male focus groups to assess the appeal of the pilot program. Findings suggested that students relate best to peers viewed in their natural environment with minimal scripted scenes. They preferred health messages in which someone was not talking at them, but rather demonstrating the skills necessary to incorporate nutritious foods into their meals and snacks. The cooking scenes were well-received by student audiences and included recipes that they felt were simple, and realistic. Results from these focus groups support the recent trend in the popularity of cooking shows and reality television for young adult audiences. Four 15-minute episodes of Good Grubbin', a theory-driven (Social Learning Theory) cooking program, were developed. This program was aimed at college students living off campus and was designed to influence students' knowledge, attitudes, and behaviors regarding eating fruits, vegetables as well as cooking skills and meal planning. Students were recruited from upper-level non-health courses to participate in a randomized control trial with pre, post and follow-up tests. The intervention group (n=50) watched four weekly episodes of the cooking show, Good Grubbin'. The control group (n=51) watched four weekly episodes on sleep disorders. Changes in knowledge, attitudes, and behaviors regarding eating fruits, vegetables, cooking and meal planning were assessed using a FFQ and a personal factors survey. A program feedback survey was used to determine acceptance of the show series by the target audience. There were significant improvements in knowledge of fruit and vegetable recommendations in the intervention group compared to the control group post intervention and at 4-month follow-up (p<0.05). The intervention group had no significant changes in attitudes or behaviors surrounding fruits, vegetables and cooking at follow-up. The cooking program was well-received by the target audience with 61% of students in the intervention group reporting an interest in viewing additional episodes of Good Grubbin'. A television show on nutrition and cooking may be influential in changing students' knowledge, but seems to have little impact on dietary behaviors. With a recent increase in popularity of cooking shows, future research should investigate the impact an extended cooking and nutrition show series might have on young adult viewers.
Keywords: nutrition